The ILCA forage evaluation scheme - Lazier, John R. (Australian Centre for International Agricultural Research, 1990)
Presents the organisation of germplasm evaluation at ILCA which shows the relationships between disciplines and activities in the Animal Feed Resources Thrust. Discusses the five steps of the evaluation scheme. Step 1 includes plantings of unselected germplasm solely for evaluation as well as those for both seed increase and initial evaluation. Step 2 consists of early multilocational trials of selected materials, step 3 involves yield trials of elite materials, trials to determine fertilizer responses, adaptation, Rhizobium relationships and yield responses. On-station farming systems trials are step 4 and on-farm studies are step 5.